An accurate measurement of the dipole orientation in various organic semiconductor films using photoluminescence exciton decay analysis. Issue 13 (18th March 2019) - Ko, Ik Jang; Lee, Hyuna; Park, Jin Hwan; Kim, Gyeong Woo; Lampande, Raju; Pode, Ramchandra; Kwon, Jang Hyuk
Abstract : In this study, we report an accurate and more reliable approach to estimate the dipole orientation of emitters especially phosphorescence, fluorescence and even thermally activated delayed fluorescence. Abstract : In this study, we report an accurate and more reliable approach to estimate the dipole orientation of emitters especially phosphorescence, fluorescence and even thermally activated delayed fluorescence. The dipole orientation measurements are performed by examining the variation of the photoluminescence (PL) exciton decay rate from time-resolved PL and optical analysis. Our anisotropic dipole orientation results are consistent with those of previous reports. The studied measurement approach is very reliable and accurate to estimate the dipole orientation of any organic semiconductor materials regardless of whether they are doped or neat films.